Nuclear energy for sustainable development: SWOT analysis on Ghana's nuclear agenda - Ephraim Bonah Agyekum; Michael Nii Sanka Ansah; Kwame Bright Afornu (Energy Reports, 2020)
The development of clean and sustainable energy around the world has become a necessity as a result of the negative effect energy generated from fossil fuel have on the environment. Ghana intends to add nuclear power to its generation mix by 2029. This paper uses the SWOT analysis tool to assess the internal strengths and weaknesses as well as the external opportunities and threats in the country relative to its nuclear power program. We found out that despite the country's effort towards meeting the requirements for the licensing, contracting, construction and operation of the facility, there are still some important loopholes which could delay the process. The research found out that Ghana has a lot of strengths and opportunities that makes an investment in nuclear power an economically viable option. However, issues such as porous security system, corruption, porous borders and policy discontinuity due to changes in political power are threats to the smooth implementation and operation of a nuclear power plant. The research therefore recommended to the government of Ghana to pay critical attention to some of these loopholes. We also looked at a particular weakness which is financing and provided some funding options for its development.
Keywords: 330; Nuclear power plant; Ghana; SWOT analysis; Sustainable energy; Financing model